Development of Kampung Qur'an as a Center for Education and Moral Guidance for the Young Generation of Jangkang Village, Bantan District, Bengkalis Regency - Andriyus; Roni Sahindra; Khairizal; M. Ridho Azzaki; Selvia Lestari; Fabella Alya Chairunnisa (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2026)
This community service program aims to develop Kampung Qur'an Jangkang as a center for religious guidance in order to improve the morals of the younger generation. The main problems faced are the limited number of structured moral guidance programs and the low intensity of religious guidance for teenagers in the community. The community service was carried out using a participatory approach, with stages including identification of community needs, program planning, implementation of activities, and evaluation. The activities carried out included Quran reading and writing coaching, Quran memorization, strengthening Islamic moral values, character training based on role models, and ongoing mentoring by religious leaders and facilitators. The results of the activities showed an increase in Quranic literacy skills, an increase in understanding of Islamic moral values, and a change in the behavior of the younger generation towards being more disciplined, polite, and religious. In addition, Kampung Qur'an Jangkang has developed into an active and sustainable center for religious activities. The conclusion of this activity is that the development of Kampung Qur'an is effective as a model for community empowerment in building the character and morals of the younger generation, and has the potential to be replicated in other areas with similar social characteristics.